Coconut Flesh Remover Technology Blueprint / Siti Nur Auni Husna Shikh Mohd Noor - Shikh Mohd Noor, Siti Nur Auni Husna (2020)
This company produces a coconut flesh remover that comes with a feature of comfortable grip for long term use and do not cause any injury to the users. The design and style of this product is unique. This is a superior quality and design at affordable price. The product, design and finishes will continue to evolve based on consumer trends and demands.